PENGARUH KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH TERHADAP KINERJA GURU MELALUI MOTIVASI KERJA GURU - Siemze Joen; Purnamawati; Amiruddin (UNM Journal of Technology and Vocational, 2022)
This study aims to describe the influence of the principal's transformational leadership on teacher performance through teacher work motivation at SMK Negeri 5 Gowa. The research uses quantitative methods with statistical analysis and structural equation modeling-partial least squares analysis to answer hypotheses. The population in this study was all teachers of SMK Negeri 5 Gowa and theresearch sample amounted to 51 teachers. The results showed: 1) there was a positive and significant influence of 30.2% of the principal's transformational leadership on teacher performance; and 2) there was a positive and significant influence of 19.5% of the principal's transformational leadership on teacher performance through teacher work motivation. This study shows that the role of teacher work motivation is partial mediation. The transformational leadership of the principal improves teacher performance through the role of teacher work motivation. The transformational leadership of the principal in improving the quality of education at SMK Negeri 5 Gowa is getting better. A principal's transformational leadership style can have a significant impact on teacher performanceand teacher work motivation resulting in teacher growth and empowerment.